Tingkat Diversifikasi Usaha Tani di Daerah Hulu, Tengah, dan Hilir Daerah Irigasi Mambal - WIJAYANTI, PUTU UDAYANI; DJELANTIK, AAA WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.2, April 2016, 2016)
Abstract Business Diversification of Farmregions in the Upstream, Midstream, and Downstream Regional Irrigation Mambal Diversification of farming is one of the main programs of agricultural development . Program development of diversification of farming in paddy fields is one of the strategies in an effort to stabilize farm income , expansion of employment opportunities and poverty reduction  (Pakpahan , 1990) . Seeing the importance of diversification for the stability of farmers 'income , it is interesting to study how to diversify farming in Mambal Irrigation Area, ( the upstream, midstream and downstream ) and their effects on farmers' income. The specific purpose of this study was to determine the level of farm diversification in the upstream, midstream , and downstream in the flow of irrigation Mambal farm diversification and determine the effect on the income of farmers in the upstream, midstream , and downstream in the flow of irrigation Mambal . The location determination is done intentionally ( purposive ) . The population in this study are all farmers who diversify his farming business .. population is three Subak is Ayung Buduk , Sembung , and Canggu . Then a total of 30 farmers selected proportionally according to the third area of the water control system , so it can be said to represent the entire population, which in this study serve as a peasant family research unit . Analysis of the data used in this research is the analysis of qualitative data is used to determine the field conditions and constraints encountered , as well as farmers' perceptions of diversification and quantitative analysis is used to determine the level of diversification and income . Results from this study was the influence of diversification of the income of farmers in the research area , as well as the absence of barriers in the irrigation water.
Keywords: diversification; farming; farmers; revenue; irrigation